Structure-activity relationship studies of Bz amide-containing α-GalCer derivatives as natural killer T cell modulators. Issue 8 (15th April 2019) - Kishi, Junichiro; Inuki, Shinsuke; Hirata, Natsumi; Kashiwabara, Emi; Yoshidome, Daisuke; Ichihara, Osamu; Fujimoto, Yukari
Graphical abstract: Abstract: Abstract: CD1d is a non-polymorphic antigen-presenting glycoprotein that recognizes glycolipids as ligands. Ligands bind to the hydrophobic grooves of CD1d, and the resulting ligand-CD1d complexes activate natural killer T (NKT) cells by means of T cell receptor recognition, leading to the secretion of various cytokines. However, details of the ligand recognition mechanism of a large hydrophobic ligand binding pocket and the relationship between cytokine induction and ligand structure are unclear. We report the synthesis of α-GalCer derivatives containing a Bz amide group having various substituting groups in the ceramide moiety, and the analysis of the structure-activity relationships. The assays reveal that the Bz amide-containing CD1d ligands function as NKT cell modulators displaying Th2 cytokine biasing responses. Furthermore, molecular dynamics simulation studies suggest that the phenyl groups can interact with the aromatic amino acid residues in the lipid binding pocket of CD1d.